PERANCANGAN TEKANAN UDARA POSITIF PADA KABIN MOBIL MSSC (MOBILE SWAB SAMPLING CHAMBER) - Fahmi Rais; Radhian Krinsnaputra; Sugiyanto Sugiyanto; F.X. Sukidjo; Stephanus Danny Kurniawan; Isworo Djati (Jurnal Rekayasa Mesin, 2022)
MSSC (Mobile Swab Sampling Chamber) car should have a fulfilling requirement as a protective isolation room or positive pressure room. A positive pressure room is needed so the virus or bacteria that is carried by the patient outside the car could not enter and contaminate the medical officer inside the car. Based on that need, the MSSC car is designed so that it can be used as a swab test sampling and having a positive pressure. The designing process was started by assembling each part of the car cabin that was used as an examination tool and positive pressure maker. This design was then simulated using the CFD method to find out whether the car cabin design produces positive pressure. The velocity of the AC blower and the percentage of exhaust openings were varied so that suitable air pressure was obtained. Based on the analysis of the simulation results, it was known that the design of the car cabin that had been done could produce positive air pressure. This positive air pressure was obtained when the blower speed was low and the exhaust opening was 100%. The value of air pressure under these conditions was 101019 Pa or +19 Pa from the ambient air that have 101000 Pa in Yogyakarta.